Prospects and constraints experienced in organic farming by farmers - GHANGHAS, B S; ROHILA, A K; CHAHAL, P K; MUKTESHWAR, RATI (The Indian Journal of Agricultural Sciences, 2021)
The world has conceded that growing demand for safe and healthy food in changing climate scenario could only meet out through organic farming. The purpose of this study was to find out prospects and constraints experienced in organic farming by farmers of Haryana. The study was carried out during 2019-20 in Hisar, Sirsa, Bhiwani, Kurukshetra, Sonipat and Yamunanagar districts of Haryana state of India. Present study concluded that organic farming was perceived highly prospective especially as environment friendly, improves soil health, products are safe, healthy and nutritious. Study also concluded that farmers were facing very serious constraints, viz. no special incentive or remunerative price policy by the government, predominance of the inorganic farmers in the locality, lack of mobilization of organic farmers and inclination towards use of chemical pesticides due to their high visual impact. Ensured remunerative price policy by government is pivotal for speedy promotion of such eco-friendly, sustainable and profitable farming.